ANALISIS MEDIA SOSIAL DAN INFLUENCER DALAM PENYEBARAN INFORMASI BENCANA BANJIR BANDANG DI ACEH: KAJIAN TEORI TWO-STEP FLOW - Hafit, Muhammad Fairuz Asra; Saleh, Muhammad; Darmadi, Darmadi (Linimasa : Jurnal Ilmu Komunikasi, 2026)
This study analyzes the role of social media and local influencers as opinion leaders in disseminating information about the flash floods in Aceh caused by Cyclone Senyar from late 2025 to early 2026, using the Two-Step Flow Theory proposed by Lazarsfeld and Katz (1948). A qualitative method was employed, involving multiple case studies with NVivo 12 content analysis, in-depth interviews, observations on Instagram and TikTok, and secondary data from BPBD and BNPB. The findings indicate that influencers such as Sherly Annavita, Vilmei, and Ferry Irwandi effectively filtered mass media information, raised more than IDR 10 billion in donations, reduced the spread of hoaxes, and addressed issues of terrorism and public distrust toward the government. These findings highlight the importance of collaboration between BPBD and influencers to enhance disaster mitigation strategies and communication in disaster-prone areas such as Aceh.